A linear stability study of stellar rotating spheres. Issue Volume 14:Issue S351(2019) (May 2019) - Rozier, Simon; Fouvry, Jean-Baptiste; Breen, Philip G.; Varri, Anna Lisa; Pichon, Christophe; Heggie, Douglas C.
Abstract: Recent observations of globular clusters imposed major revisions to the previous paradigm, in which they were considered to be isotropic in velocity space and non-rotating. However, the theory of collisionless spheroids with some kinematic richness has seldom been studied. We present here a first step in this direction, owing to new results regarding the linear stability of rotating Plummer spheres, with varying anisotropy in velocity space and total amount of angular momentum. We extend the well-known radial orbit instability to rotating systems, and discover a new regime of instability in fast rotating, tangentially anisotropic systems.